IMPLEMENTATION OF QANUN JINAYAT WITHIN THE FRAMEWORK OF SPECIAL AUTONOMY IN ACEH - Nurul Kamaly; Vania Balqies; Aril Al Shufi; Dinda Maghfirah; Ibnu Phonna Nurdin (Master Program of Sociology, Universitas Malikussaleh,, 2026)
Aceh Province has special authority to implement Islamic law based on the 2006 Aceh Government Law. This is then strengthened by regional regulations (qanun), including Aceh Qanun Number 6 of 2014 concerning Jinayat Law. However, the implementation of Qanun Jinayat still faces various institutional and social challenges that affect its effectiveness. This study aims to analyze the implementation of Qanun Jinayat within the framework of special autonomy in Aceh and identify the factors influencing its effectiveness. This research uses a qualitative approach with a literature study method, analyzed using policy implementation theory. Data were collected from various relevant written sources, including laws and regulations, books, and scientific journals, and analyzed using descriptive qualitative techniques through data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of Qanun Jinayat has been formally supported by a clear institutional structure; however, its implementation has not yet been optimal. This condition is influenced by limited resources, suboptimal coordination among institutions, differences in understanding among implementing officers, and limited legal socialization within society. In addition, the increasingly critical mindset of society also poses challenges to the implementation of Qanun Jinayat. Therefore, strengthening institutional capacity and improving legal socialization strategies are necessary to support more effective and sustainable implementation in Aceh.